FACTORS AFFECTING LAND FUNCTION OUTSOURCING FROM COCOA FARMING BUSINESS TO PATCHOULI FARMING AT THE VILLAGE KUKUTIO WATUBANGGA DISTRICT OF KOLAKA - Kabul Budiman; Nursalam Nursalam; Andik Prasetiyono (Agribusiness Journal, 2016)
This study aims to determine the factors that affects over the function of farming land of nilam in the village Kukutio Watubangga District of Kolaka. The results of the research that has been done using models of multiple linear regression analysis showed that the independent variables which consists of the price of cocoa (X1), the price of nilaim (X2), age of farmers (X3), experience of cocoa farmers (X4), the experience of nilam farmers (X5), and education level of farmers (X6), are simultaneously significant effect on the dependent variable that is of land conversion (Y).